Butterfly proboscis-inspired tight rolling tapered soft actuators. Issue 12 (15th January 2019) - Sol, Jeroen A. H. P.; Peeketi, Akhil R.; Vyas, Nihit; Schenning, Albertus P. H. J.; Annabattula, Ratna K.; Debije, Michael G.
Abstract : Tight bending bio-inspired soft actuators were fashioned in liquid crystalline networks by using a novel tapered film geometry. Abstract : Liquid crystalline networks have been fashioned into thin films with tapered thicknesses, revealing the possibility of rolling up extremely tightly when triggered thermally or with light. Compared to the often limited bending shown previously in liquid crystal network actuators, these tapered films curl up several hundreds of degrees. Finite element results of simulated functionally graded thin films with tapered thicknesses corroborate well with experimental work.